INDUSTRIAL VALUE CHAIN IN INDONESIA’S SME CREATIVE BUSINESS: AN EXPLORATION RESEARCH - Ivan Evander Subagyo; Dewi Savitri Saraswati; Teddy Trilaksono (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2019)
The creative industry is currently growing very rapidly in developing countries. This is indicated by various government policies to increase the competitiveness of this industry. Value chains are needed to gain the competitive advantage within this industry at every additional step of the chain. However, there is no comprehensive research on the creative industry value chain in developing countries, such as Indonesia, especially in small and medium enterprises (SMEs). This study attempts to explore the concept of industrial chain values to narrow the gaps that exists in the literature. The research method used is a qualitative approach through semi-structured interviews and observations of 11 SMEs consisting of 5 creative business sub-sectors, namely the culinary, fashion, craft, photography, and visual communication design sectors. The results of this study indicate that, in creative industries, co- creation is the differentiator on the value chain activities, especially those that offer customization. Meanwhile, the use of social media is also considered as an important value chain activities that must be used to effectively communicate the value of the business. The results of this study can be used by stakeholders in Indonesian SMEs as a reference for formulating competitiveness strategies for this creative industry.